(untitled) (Medical Forum Monthly, 2020)
Objective: To study the Histological Pattern of Central Nervous system Neoplasms. Study Design: Retrospective study. Place and Duration of Study: This study was conducted at the Section of Histopathology, Aziz Bhatti Teaching Hospital Gujrat and Idris Teaching Hospital Sialkot to check the frequency of all Central Nervous system neoplasms diagnosed here from January 2014 to December 2019. Materials and Methods: A total of 451 Central Nervous system neoplasms were diagnosed. All samples were fixed in ten percent buffered formalin. Routinely processed under standard conditions for paraffin embedding, sectioned and finally stained with haematoxylin and eosin using standard procedures. When required, special stains such as PAS, reticulin etc. and immunohistochemistry by PapanicouIaeu technique using monoclonal antibodies against Glial fibrillary acidic protein, a wooden plaque bearing a prayer, Cytokeratins, Life-cycle assessment, Pan B and T etc. were performed. The histological characterisation of Central Nervous system tumors was done according to the World Health Organization histological typing of tumors of the Central Nervous system7. The grading of astrocytic neoplasms was done according to the Kernohan grading systems for astrocytomas11. Results: In case of primary Central Nervous system Neoplasmas highest incidence of the Glial tumours 41.01% and minimum incidence of primary Central Nervous system Neoplasms was Miscellaneous tumours 8.98 %. In case of Glial Neoplasms the highest incidence was of Astrocytomas 45.61% and lowest incidence was Gliosarcomas 3.50%. In case of Astrocytic Neoplasms the highest incidence of Grade 3-4 astrocytomas 49.29% and lowest incidence was Subependymal giant cell astrocytomas 1.40%. In case of Miscellaneous CNS neoplamas the highest incidence was of Hemangioblastomas 29.03% and lowest incidence was Endothelial tumours (Hemangiopericytomas)3.22%, Melanocytic Tumours (Malignant Melanoma) 3.22% and Pineal Parenchymal Tumours (Pineoblastoma) 3.22%. In case of 5 commonest categories of primary CNS Neoplasms the mean age was maximum 43.34 in age range 2-75 years and was minimum in age range 1-37 years (13.01). Conclusion: Except for the high percentages of anaplastic recapitulate the appearance of the normal resident oligodendroglia of the brain & A type of brain tumor that begins in cells lining spinal cord central canal and the low percentage of metastatic tumours, most of our findings roughly concide with the published data (JPMA: 1 54;2001).